How to organise student learning groups - Association for Supervision and Curriculum Development (Alexandria, VA : ASCD, 2000)
This video examines different types of grouping strategies. Classroom teachers provide real examples of how to use Mastery groups to help students learn new information, use cooperative learning group to build teamwork and use problem solving groups to involve students in their own learning
Title from title screen
Copy available in DVD format
Keywords: Group work in education; Teaching and learning